Constraint Satisfaction Problem in Matrices with COP: Interval Assignments and Matrices with COP (Journal of Advances and Scholarly Researches in Allied Education, 2019)
We consider the accompanying imperative fulfillment issue Given a set F of subsets of a limited set S of cardinality n, and an assignment of intervals of the discrete set {1, . . . , n} to each of the subsets, does there an exist a bijection f s ⟶{1,….n} to such an extent that for every component of F, its picture under f is same as the interval alloted to it. An interval assignment to a given arrangement of subsets is called plausible if there exists such a bijection. In this paper, we describe doable interval assignments to a given arrangement of subsets. We at that point utilize this outcome to describe matrices with the Consecutive Ones Property(COP), and to portray matrices for which there is a stage of the rows with the end goal that the columns are altogether arranged in rising request. We additionally present a portrayal of set frameworks which have a possible interval assignment.